Parental Strategies in Fostering Children’s Literacy Habits in the Digital Era: A Qualitative Study of Urban Families - Dinda Ayu Kusumaningrum; Ahmad Fikri Ramadhan; Melati Puspita Anjani (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study examined parental strategies in fostering children’s literacy habits in the digital era within urban families. A qualitative case study design was employed, involving 12 families with elementary–school–aged children. Data were collected through semi-structured interviews, limited observations, and supporting documentation, and were analyzed using thematic analysis through systematic coding, categorization, and theme development. The findings identified four principal strategies: structuring a home literacy environment, negotiating digital device use, positioning reading as a relational activity, and adapting literacy routines to time constraints shaped by urban work patterns. The results indicated that sustained literacy habits were formed through integrated, dialogic, and adaptive practices rather than rigid technological control. Family literacy in the digital era emerged as a socially negotiated practice embedded in everyday routines and influenced by urban dynamics. The study contributes conceptually to the development of the home literacy environment framework in digital contexts and offers practical implications for family-based literacy programs.